Basaloid squamous cell carcinoma of the anus: a case report - Pires, Guida C.; Silva, André A.; Simões, Liliana V.; Lourenço, Beatriz R.; Rocha, Catarina C.; Meireles, Lília J. (International Surgery Journal, 2025)
Anal cancer, which affects the anus, anal canal, or anorectum, represents ∼2.2% of all gastrointestinal malignancies. Squamous cell carcinoma (SCC) is the most common type of anal cancer. Basaloid SCC is a rare and aggressive variant of the SCC, which is mainly seen in the upper aero digestive tract and the anal canal. These carcinomas are characterized by marked histological undifferentiation and a heightened proliferation rate. Macroscopically, appear as a perianal ulcer or a mass with raised edges and ulceration, often misdiagnosed as hemorrhoidal disease. Despite its rarity, accurate diagnosis is crucial. In the literature, there are only few case reports with such aggressive cancer having good outcomes with chemoradiation therapy. Owing to its infrequency, we present a case of basaloid SCC of the anus in a female patient with poor outcomes, alongside a comprehensive literature review.